2016
DOI: 10.1177/0047239515626371
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Flipped Classroom in High School Health Education

Abstract: As advanced technology increasingly infiltrated into classroom, the flipped classroom has come to light in secondary educational settings. The flipped classroom is a new instructional approach that intends to flip the traditional teacher-centered classroom into student centered. The purpose of this research is to investigate the impact of the flipped classroom instructional pedagogy in a ninth grade health education class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
81
0
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 5 publications
4
81
0
23
Order By: Relevance
“…Then, most class time is spent on group learning activities that are focusing on applying the knowledge learned from the video lectures, such as solving advanced problems with the support of the teacher and peers or working on projects. Additional in-class activities include but are not limited to individual practices, student presentations, and taking quizzes.Even though after-class activity is not common in the flipped classroom model, the review of the literature shows that some teachers practice completion of self-evaluation or reflection as an after-class activity (Bhagat, Chang & Chang, 2016;Clark, 2015;Lai & Hwang, 2016;Mazur, Brown & Jacobsen, 2015;Schultz, Duffield, Rasmussen & Wageman, 2014;Wang, 2016).The benefits of the flipped teaching method in the current literature are listed as follows:(1) students move at their own pace, (2) doing 'homework' in class gives teachers better insight into student difficulties and learning styles, (3) teachers can more easily customize and update the curriculum and provide it to students 24/7, (4) classroom time can be used more effectively and creatively, (5) teachers using the method report seeing increased levels of student achievement, interest, and engagement, (6) learning theory supports the new approaches, and (7) the use of technology is flexible and appropriate for 21st century learning (Chao, Chen & Chuang, 2015;Chen, 2016;Fulton, 2012;Snyder, Paska & Besozzi, 2014;Tsai, Shen & Lu, 2015). …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Then, most class time is spent on group learning activities that are focusing on applying the knowledge learned from the video lectures, such as solving advanced problems with the support of the teacher and peers or working on projects. Additional in-class activities include but are not limited to individual practices, student presentations, and taking quizzes.Even though after-class activity is not common in the flipped classroom model, the review of the literature shows that some teachers practice completion of self-evaluation or reflection as an after-class activity (Bhagat, Chang & Chang, 2016;Clark, 2015;Lai & Hwang, 2016;Mazur, Brown & Jacobsen, 2015;Schultz, Duffield, Rasmussen & Wageman, 2014;Wang, 2016).The benefits of the flipped teaching method in the current literature are listed as follows:(1) students move at their own pace, (2) doing 'homework' in class gives teachers better insight into student difficulties and learning styles, (3) teachers can more easily customize and update the curriculum and provide it to students 24/7, (4) classroom time can be used more effectively and creatively, (5) teachers using the method report seeing increased levels of student achievement, interest, and engagement, (6) learning theory supports the new approaches, and (7) the use of technology is flexible and appropriate for 21st century learning (Chao, Chen & Chuang, 2015;Chen, 2016;Fulton, 2012;Snyder, Paska & Besozzi, 2014;Tsai, Shen & Lu, 2015). …”
mentioning
confidence: 99%
“…On the other hand, the current literature also shows that not all flipped courses result in success/satisfaction. While some studies found no significant difference in student achievement between the flipped classroom and traditional classroom (Chen 2016;Clark 2015;Desantis et al, 2015;Kirvan et al, 2015), others resulted in a detrimental or inferior effect on student achievement (ArnoldGarza, 2014;Frederickson, Reed, & Clifford, 2005;Jaster, 2013;Johnson & Renner, 2012).Studies show that students are generally satisfied with the use of the flipped classroom approach. Qualitative comments from these studies suggest that the new way of watching videos before class and working through advanced problems in the classroom with peers is the most important feature that contributed to a high satisfaction of the flipped courses (Bhagat et al, 2016;Schultz et al, 2014;Snyder et al, 2014;Clark, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The FCR is a new approach in instruction that designed to flip the traditional learning classroom from Teacher-centered into Student-centered (Chen, 2016). FCR approach has four different elements: "FLIP" ("F"lexible Environment), It refers to facility of place, time and of learning.…”
Section: Introductionmentioning
confidence: 99%